Estimating neonatal length of stay for babies born very preterm - Seaton,SE; Barker,L; Draper,ES; Abrams,KR; Modi,N; Manktelow,BN; UK,Neonatal Collaborative (Archives of Disease in Childhood. Fetal and Neonatal Edition, 2019)
OBJECTIVE: To predict length of stay in neonatal care for all admissions of very preterm singleton babies. SETTING: All neonatal units in England. PATIENTS: Singleton babies born at 24-31 weeks gestational age from 2011 to 2014. Data were extracted from the National Neonatal Research Database. METHODS: Competing risks methods were used to investigate the competing outcomes of death in neonatal care or discharge from the neonatal unit. The occurrence of one event prevents the other from occurring. This approach can be used to estimate the percentage of babies alive, or who have been discharged, over time. RESULTS: A total of 20 571 very preterm babies were included. In the competing risks model, gestational age was adjusted for as a time-varying covariate, allowing the difference between weeks of gestational age to vary over time. The predicted percentage of death or discharge from the neonatal unit were estimated and presented graphically by week of gestational age. From these percentages, estimates of length of stay are provided as the number of days following birth and corrected gestational age at discharge. CONCLUSIONS: These results can be used in the counselling of parents about length of stay and the risk of mortality.